Peran Pekerjaan Sosial dalam Mengatasi Perdagangan Manusia - Adi Fahrudin; Dayne Trikora Wardhani; Rini Hartini Rinda Andayani (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Trafficking in human beings is a vast and complex problem that requires a multidimensional approach to effective intervention. This abstract explores the role of social work in dealing with human trafficking based on the synthesis of relevant literature. Social workers play an important role in combating human trafficking by identifying victims, providing a victim-centric approach, and offering comprehensive services to crossers. They play an important role in raising awareness, advocating policy change, and promoting social justice initiatives to address the root causes of human trafficking. Through their dedication to the promotion of human rights, social justice, and empowerment, social workers make a significant contribution to combating human trafficking.